DISASTERS & PSYCHOLOGICAL TRAUMA — CHALLENGE FOR PAKISTAN - Ali, Sohail (Journal of Pakistan Psychiatric Society, 2008)
Psychological trauma, a new concept, came to Pakistan in the early 1990s when Karachi was under going crisis alongwith other social, geo-cultural and ethnic issues. This remained unrecognized generally until the devastating earthquake in October 2005 for which National Plan of Action for Earthquake Survivors was drafted that included model of emergency and post emergency response based on a 8 point model. In February 2007, the first national Centre for Trauma Research and Psychosocial Interventions (CTRPI) was established which is carrying out indigenous research projects and training activities. This article aims to examine the present efforts to address the trauma related mental health problems in Pakistan, identify the challenges we are facing and suggest future directions for services and research. The article also aims to raise awareness and debate about a crucial area of mental health which has become increasingly important with on going voilence in Pakistan but is largely neglected.